2022
DOI: 10.1002/ange.202207252
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Engineering for the Electrocatalytic CO2 Reduction Reaction

Abstract: Rather than just focusing on the catalyst itself in the electrocatalytic CO 2 reduction reaction (eCO 2 RR), as previously reviewed elsewhere, we herein extend the discussion to the special topic of the microenvironment around the electrocatalytic center and present a comprehensive overview of recent research progress. We categorize the microenvironment based on the components relevant to electrocatalytic active sites, i.e., the catalyst surface, substrate, co-reactants, electrolyte, membrane, and reactor. Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 301 publications
(250 reference statements)
0
8
0
Order By: Relevance
“…51 There are already some reviews recognizing the significance of the microenvironment and summarizing the study of regulating the microenvironment in CO 2 RR. [52][53][54] In this review, we will extend the scope to the common issues of gas-involving electrocatalysis, including CO 2 RR and NRR. Moreover, we precisely classify the multifactors affecting catalytic activity and selectivity in heterogeneous catalytic systems into gas diffusion, proton supply, and electron transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 There are already some reviews recognizing the significance of the microenvironment and summarizing the study of regulating the microenvironment in CO 2 RR. [52][53][54] In this review, we will extend the scope to the common issues of gas-involving electrocatalysis, including CO 2 RR and NRR. Moreover, we precisely classify the multifactors affecting catalytic activity and selectivity in heterogeneous catalytic systems into gas diffusion, proton supply, and electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In the holistic reaction process, several critical factors in this microenvironment are coupled with each other, collectively affecting the behavior of substances (gas, proton, and electron) and the activity and selectivity of electrocatalysis 51 . There are already some reviews recognizing the significance of the microenvironment and summarizing the study of regulating the microenvironment in CO 2 RR 52–54 . In this review, we will extend the scope to the common issues of gas‐involving electrocatalysis, including CO 2 RR and NRR.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the gas (CO 2 )–liquid (aqueous solution)–solid (photocatalyst) three-phase reaction systems have been developed to address the limited CO 2 mass transfer issue in water. ,, The introduction of the gas layer to the liquid–solid boundary was found highly efficient in increasing the local concentration and diffusion rate of CO 2 while diluting the proton content near the catalyst surface, resulting in improved CO 2 RR activity and selectivity. , Iizuka et al reported a method to construct a three-phase interface by continuously bubbling CO 2 throughout the photoreactions, but the system required constant energy consumption to maintain . It was found that the three-phase interface could be regulated by simply tuning the hydrophobic property of the catalyst, substrate, or surface modifier. ,, For instance, a Pt-loaded photocatalyst modified with a hydrophobic ligand exhibited significant CO 2 RR promotion and HER inhibition due to efficient three-phase contact of CO 2 , water, and catalyst . Recently, fast delivery of CO 2 gas to the catalyst was reported by constructing a hydrophobic–hydrophilic abrupt interface on the hydrophobic substrate .…”
Section: Introductionmentioning
confidence: 99%
“…22 It was found that the three-phase interface could be regulated by simply tuning the hydrophobic property of the catalyst, substrate, or surface modifier. [16][17][18]23,24 For instance, a Ptloaded photocatalyst modified with a hydrophobic ligand exhibited significant CO 2 RR promotion and HER inhibition due to efficient three-phase contact of CO 2 , water, and catalyst. 17 Recently, fast delivery of CO 2 gas to the catalyst was reported by constructing a hydrophobic−hydrophilic abrupt interface on the hydrophobic substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation